2022
DOI: 10.3389/fmicb.2022.908257
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Drivers of the Soil Microbial Diversity and Composition in Primary Old-Growth Forest and Secondary Woodland in a Subtropical Evergreen Broad-Leaved Forest Biome in the Ailao Mountains, China

Abstract: Replacement of primary old-growth forests by secondary woodlands in threatened subtropical biomes drives important changes at the level of the overstory, understory and forest floor, but the impact on belowground microbial biodiversity is yet poorly documented. In the present study, we surveyed by metabarcoding sequencing, the diversity and composition of soil bacteria and fungi in the old-growth forest, dominated by stone oaks (Lithocarpus spp.) and in the secondary Yunnan pine woodland of an iconic site for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…We have shown in our companion study (Zeng et al, 2022) that the edaphic features, such as soil pH and nutrient content, were significantly different in the Lithocarpus old-growth forest by comparison to the Pinus woodland. These differences in edaphic features influenced the soil microbial communities (Zeng et al, 2022), but also the ECM microbial communities (present study) as shown in other forest ecosystems (Peay et al, 2013;Liu et al, 2014Liu et al, , 2015He et al, 2017). Given that soil microbial communities feed the plant microbiome, both the reservoir of microorganisms in soil adjacent to roots and the soil edaphic Frontiers in Microbiology frontiersin.org parameters strongly influence the plant (Frey Klett et al, 2007;Bonito et al, 2014).…”
Section: Distribution Of Bacterial and Fungal Otus In Lithocarpus And...mentioning
confidence: 71%
See 4 more Smart Citations
“…We have shown in our companion study (Zeng et al, 2022) that the edaphic features, such as soil pH and nutrient content, were significantly different in the Lithocarpus old-growth forest by comparison to the Pinus woodland. These differences in edaphic features influenced the soil microbial communities (Zeng et al, 2022), but also the ECM microbial communities (present study) as shown in other forest ecosystems (Peay et al, 2013;Liu et al, 2014Liu et al, , 2015He et al, 2017). Given that soil microbial communities feed the plant microbiome, both the reservoir of microorganisms in soil adjacent to roots and the soil edaphic Frontiers in Microbiology frontiersin.org parameters strongly influence the plant (Frey Klett et al, 2007;Bonito et al, 2014).…”
Section: Distribution Of Bacterial and Fungal Otus In Lithocarpus And...mentioning
confidence: 71%
“…In addition to root exudates, hyphal exudates, such as trehalose, released by the various ECM fungi played an important role in recruiting bacterial and fungal microbiomes (Zhang et al, 2021). We have shown in our companion study (Zeng et al, 2022) that the edaphic features, such as soil pH and nutrient content, were significantly different in the Lithocarpus old-growth forest by comparison to the Pinus woodland. These differences in edaphic features influenced the soil microbial communities (Zeng et al, 2022), but also the ECM microbial communities (present study) as shown in other forest ecosystems (Peay et al, 2013;Liu et al, 2014Liu et al, , 2015He et al, 2017).…”
Section: Distribution Of Bacterial and Fungal Otus In Lithocarpus And...mentioning
confidence: 77%
See 3 more Smart Citations